HEMATOLOGICAL AND SOME BIOCHEMICAL ALTERATIONS IN SHEEP EXPERIMENTALLY INFECTED WITH CLOSTRIDIUM PERFRINGENS TYPE D INFECTION - A. A. Nasir; M. Younus; M. U. Rehman; M. Lateef; S. A. Khaliq; I. Ahmad; M. Abbas (Journal of Animal and Plant Sciences, 2013)
The study was designed to determine the hematological and biochemical changes in sheep following the experimental Clostridium perfringens type D infection. Mean leukocyte count was significantly higher (p < 0.05) between control and infected groups at 10 hours (11.2±0.3 vs 19.7±3.5), 20 hours (10.6±0.3 vs 16.9±0.2) and then started to decrease in infected group. A statistically significant increase (p < 0.05) was observed between the means within the infected for PCV at 30 hours. Mean blood glucose (74±6.7 vs 141±13.2), urea (26.3±3.5 vs 92.3±6.7) and serum creatinine 1.6±0.2 vs 7.5±1.4) levels were elevated significantly at 30 hours in group of experimentally infected animals as compared to control groups. The results of our study demonstrated that hematological values fluctuated after post experimental infection but almost remained within the normal range however, blood glucose, urea and serum creatinine levels increased significantly as the disease progressed and could be diagnostic under field conditions in animals suspected for type D enterotoxaemia.
Keywords: Clostridium perfringens type D; Sheep; RBC; WBC; Platelets; PCV; blood glucose; urea; serum creatinine